Utilizing Artificial Intelligence to Strengthen Humanitarian Digital Media at BSMI Maros Regency: Pemanfaatan Artificial Intelligence untuk Penguatan Media Digital Kemanusiaan BSMI Kabupaten Maros - Raidah Intizar Yusuf; Sariana Sariana; Basri Basri (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Limited media exposure remains a key challenge for humanitarian organizations in strengthening accountability and public trust. This community service program aimed to enhance the communication and publicity capacity of the Indonesian Red Crescent (BSMI) Maros Regency using artificial intelligence (AI) in digital media management. The novelty of this program lies in integrating AI as a strategic communication tool for humanitarian organizations, rather than merely providing general digital training, by supporting content planning, search engine optimization, and context-based publication management. The program was implemented through training and mentoring activities that combined lectures, discussions, hands-on practice, and the use of a workbook as a reflective learning instrument. The results indicate an improvement in volunteers’ understanding and skills in managing digital media more strategically, as reflected in learning evaluation outcomes and the continuity of post-training practices, including the formation of digital volunteer teams and active involvement in humanitarian content publication. Practically, this program contributes to the development of a contextual volunteer empowerment model based on digital literacy and artificial intelligence. This model has the potential to be replicated by other humanitarian organizations to strengthen accountability, enhance public trust, and support the sustainability of humanitarian initiatives in the digital communication era.